The miR-941/FOXN4/TGF-β feedback loop induces N2 polarization of neutrophils and enhances tumor progression of lung adenocarcinoma - Zhang, Xiaojing; Huang, Xitong; Zhang, Xianying; Lai, Lichang; Zhu, Baoyi; Lin, Peibin; Kang, Zhanfang; Yin, Dazhong; Tian, Dongbo; Chen, Zisheng; Gao, Jun (Frontiers in Immunology, 2025)
BackgroundLung adenocarcinoma (LUAD) is a major subtype of lung cancer and one of the deadliest cancers in humans. Dysregulation of miRNA activity in tumor-associated neutrophils (TANs) in the tumor microenvironment plays an important role in the occurrence and development of LUAD.MethodIn this study, the miReact algorithm was used to analyze the single-cell RNA sequencing data of LUAD samples to reveal the miRNA profile characteristics of TANs in LUAD patients. The function of miR-941 was investigated in vivo and in vitro. The target gene and underlying signaling pathway of miR-941 were predicted and validated with qPCR, luciferase assay, WB and ELISA assay.ResultsThe results indicated the crucial role of TANs, especially N2-TANs in LUAD and miR-941 activity was significantly upregulated in TANs of LUAD patients. MiR-941 overexpression promoted the proliferation, invasion, migration and anti-apoptosis of A549 and H1299. In vivo xenograft mouse model confirmed that miR-941 overexpression enhanced the growth of tumors formed by H1299 cells. Bioinformatics analysis showed that miR-941 targeted the tumor suppressor gene FOXN4, and we confirmed that FOXN4 overexpression could counteract the malignant effects of miR-941. In addition, miR-941 may drive LUAD progression through the FOXN4/TGF-β feedback signaling loop and participate in the N2-TAN polarization.ConclusionIn summary, these findings reveal the key role of N2-TANs and the miR-941/FOXN4/TGF-β signaling loop in LUAD progression and provide potential therapeutic targets for future interventions.